The stress of caregiving: a study of family caregivers of breast cancer patients receiving oncologic treatment at a Malaysian General Hospital - Raynuha Mahadevan; Nik Ruzyanei Nik Jaafar; Siti Hazrah Selamat Din; Siti Nor Aizah Ahmad; Azlin Baharuddin; Rosdinom Razali (Universiti Kebangsaan Malaysia, 2013)
Many studies among caregivers of breast cancer patients have revealed that stress affects a significant proportion of this particular group. The situation among caregivers of breast cancer patients in Malaysia was however not known. This cross-sectional study aimed to determine the proportion of the family caregivers who experienced stress while caring for the breast cancer patients who were on oncologic treatment in Kuala Lumpur Hospital and factors which predict the stress among these caregivers. A total of 130 family caregiver-breast cancer patient dyads who were attending the Institute of Radiotherapy & Oncology, Kuala Lumpur Hospital during a 3-month study period were recruited by non-random sampling method. The caregivers’ stress was measured using the stress domain of the depression, anxiety, stress scale (DASS-21) while other data obtained included the patients’ and caregivers’ socio demographic status, the patients’ illness characteristics and the caregiving factors and the caregivers’ perceived social support. About 1 in 4 (24.6%; n=32) caregivers of breast cancer patients were stressed. Duration of caregiving, sharing of caregiving burden, patients’ age and patients’ functionality were found to be significantly associated with stress (p value <0.05). All these factors, except for duration of caregiving, continue to be significant in the logistic regression analysis (p value <0.05). This study found that a high proportion of the family caregivers experienced stress. Identification of the predictors of stress among the caregivers may help in the prevention strategies of stress in this group of caregivers.